APF and dentifrice effect on root dentin demineralization and biofilm - Vale, G C; Tabchoury, C P M; Del Bel Cury, A A; Tenuta, L M A; ten Cate, J M; Cury, J A (Journal of dental research, 2011)
Because dentin is more caries-susceptible than enamel, its demineralization may be more influenced by additional fluoride (F). We hypothesized that a combination of professional F, applied as acidulated phosphate F (APF), and use of 1100-ppm-F dentifrice would provide additional protection for dentin compared with 1100-ppm-F alone. Twelve adult volunteers wore palatal appliances containing root dentin slabs, which were subjected, during 4 experimental phases of 7 days each, to biofilm accumulation and sucrose exposure 8x/day. The volunteers were randomly assigned to the following treatments: placebo dentifrice (PD), 1100-ppm-F dentifrice (FD), APF + PD, and APF+FD. APF gel (1.23% F) was applied to the slabs once at the beginning of the experimental phase, and the dentifrices were used 3x/day. APF and FD increased F concentration in biofilm fluid and reduced root dentin demineralization, presenting an additive effect. Analysis of the data suggests that the combination of APF gel application and daily regular use of 1100-ppm-F dentifrice may provide additional protection against root caries compared with the dentifrice alone.